2018
DOI: 10.31219/osf.io/b34fw
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness and equity of Payments for Ecosystem Services: Real-effort experiments with Vietnamese land users

Abstract: Abstract:Payments for Ecosystem Services (PES) are widespread in conservation policy. In PES, environmental effectiveness and social equity are often perceived as conflicting goals. Empirical studies on the relationship between popular design features, such as payment differentiation and payment conditionality, and effectiveness and equity are scarce. Further, they struggle with measuring and separating ecological and equity outcomes. In this study, we combine two incentivized lab-in-the-field experiments with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(25 reference statements)
1
3
0
Order By: Relevance
“…That is to say, people who have not directly benefitted from the compensations (but have been exposed to the reciprocity framing) also strongly agree with the meritocratic inequality statement and simultaneously favor government action on inequality. This echoes another recent study which concluded that payments programs based on meritocratic principles need not be in conflict with equity (Loft et al 2019).…”
Section: Social Values and Beliefs: Altered Beliefs On Inequality And Gsupporting
confidence: 75%
“…That is to say, people who have not directly benefitted from the compensations (but have been exposed to the reciprocity framing) also strongly agree with the meritocratic inequality statement and simultaneously favor government action on inequality. This echoes another recent study which concluded that payments programs based on meritocratic principles need not be in conflict with equity (Loft et al 2019).…”
Section: Social Values and Beliefs: Altered Beliefs On Inequality And Gsupporting
confidence: 75%
“…Our findings are important for global conservation and sustainability goals, demonstrating the importance of payment design and nonenvironmental motivations in incentive-based conservation schemes and suggesting ways to increase effectiveness and efficiency. Policymakers should work to understand and use local equity norms, such as locally-preferred distribution criteria (52), in the design and implementation of conservation payments (13), particularly when developing targeting criteria, rules, and monitoring procedures to determine payments (69). Policy design should incorporate principles of accountability that reflect the conservation choices that land users make given their opportunities, not differences in exogenous characteristics such as previous land endowments, ethnicity, financial and administrative literacy, or power (26).…”
Section: Discussionmentioning
confidence: 99%
“…Social equity refers to fair access to resources and opportunities, and full participation in the social and cultural life of a community. It serves as a central dimension for promoting livability and viability, which is one of the main goals of sustainable development [43,44]. Top-down redevelopment emphasizes social equity, so the government adopts some special policies to improve the welfare of the local villagers, especially the most vulnerable groups [45].…”
Section: Welfare Difference Between Bottom-up and Top-down Redevelopment Modesmentioning
confidence: 99%